Critical Limb Ischemia : Acute and Chronic - Dieter, Robert S.; Dieter, Jr, Raymond A.; Dieter, III, Raymond A.; Nanjundappa, Aravinda (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive overview of acute and chronic critical limb ischemia (CLI). Loss of an extremity, or a portion thereof, is not necessarily a life-ending process, but it is a debilitating experience whether involvement is of the upper or the lower extremity. It reviews the epidemiology, pathophysiology, etiology, physical examination, imaging modalities, diagnosis, and treatment of limb ischemia. It investigates the most frequent as well as the more unusual etiological processes that may lead to the most dreaded concern of patients and families: amputation. The therapeutics of CLI has been significantly advanced through the multidisciplinary approach to the patient and disease, a focus that is explored in detail throughout the book. Surgical and endovascular treatment guidelines as well as medical therapy, wound healing, and long-term care are discussed. Featuring an extensive illustration program, Critical Limb Ischemia: Acute and Chronic, is a valuable resource for vascular and endovascular surgeons, vascular medicine specialists, interventional radiologists, and cardiologists.